ANALISIS SIFAT FISIK DAN KANDUNGAN GIZI DIMSUM IKAN KEMBUNG : (Rastrelliger sp.) - Trisnawati, Desi; Dadan Ahmad Hudaya; Marlinda Indriati; Euis Kartika (International Journal Mathla’ul Anwar of Halal Issues, 2026)
Food diversification is a strategic approach to improving a balanced and nutritious diet based on local resources. Mackerel (Rastrelliger sp.) is a rich source of animal protein in Banten Province but remains underutilized, despite its high content of protein, omega-3 and omega-6 fatty acids, as well as essential vitamins and minerals. This study aimed to evaluate the organoleptic characteristics and nutritional content of dim sum made from mackerel as a form of marine-based food diversification. The research was conducted experimentally using a Completely Randomized Design (CRD) consisting of five treatment formulations with varying ratios of mackerel and chicken (P0 to P4), each tested in two replications. Observed parameters included organoleptic tests, proximate analysis (moisture, ash, protein, fat, carbohydrates, and iron), total energy calculation, and contribution to Recommended Dietary Allowance (RDA). The results showed that formulation P1 achieved the best scores in organoleptic attributes (color, aroma, taste, and texture) and had higher protein (28.44%), fat (4.80%), and iron (152.23 ppm) content compared to the control. The RDA contribution per 100 g of dim sum P1 included 47.40% protein, 7.16% fat, 2.84% carbohydrates, and 9.02% total energy. Mackerel based dim sum demonstrated high nutritional value and consumer acceptability, indicating its potential for development as a healthy and functional processed food product utilizing local marine resources.